(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Background: The incidence of hypertension is found to be large in the growing country. Overweight and obesity are now becoming a public health concern, and hypertensive conditions have been associated with obesity and overweight. Aim: Nutritional Assessment of Hypertensive Patients. Hypertension patients are not fully cautioned about their daily recommended intake. Adequate prevention is mandatory to prevent or manage such health problems. So it is important to assess the nutritional status of hypertension patients. This suggests that the patients deliberately reduced the number of consumed foodstuffs. Objective: 1. To assess the nutritional status of hypertension patients . 2. To find out the association between the nutritional status of the hypertensive patients and demographic variables. Material and Method: The research approach used for the study was a quantitative research approach. A descriptive study design was used for the study was conducted at a tertiary care hospital in western Maharashtra. The sample size should be chosen with the help of a simple random sample. 80 hypertension patients were selected by purposive sampling technique. The data were collected by structured questionnaires. The data were analyzed using descriptive& inferential statistics. Result: The result showed that among all study participants Patients diagnosed with hypertension are 52 normal, 26 overweight, 1 obese, and 1 underweight, which was also confirmed by observations. At the same time, dietary energy intake was found to be insufficient compared to the recommended allowances. 66 hypertension patients belong to a poor category, and only 14 hypertension patients belong to a good category.